Associação da sox2 no prognóstico e sobrevida em pacientes com carcinoma de células escamosas oral: uma revisão sistemática e metanálise - Fernandes, Jefferson Douglas Lima (2023)
Oral squamous cell carcinoma (OSCC) accounts for more than 90% of all oral malignancies and considered a public health problem, associated with a low survival rate. Several genetic and environmental factors are involved in the process of oral carcinogenesis, and SOX2 (SRY-box transcription factor 2) has aroused great interest in the scientific community, o it is an important stem cell marker, which is associated with cell proliferation, migration, invasion, tumorigenesis, anti-apoptosis and chemoresistance. In this context, to evaluate the mechanisms of the dual role of this gene, its expression and the association with prognosis and survival in OSCC are the objectives of the present work. This systematic review and meta-analysis [PROSPERO (CRD42023431821)] included observational studies that compared the association of clinicpathologic and survival outcomes with SOX2 immunoexpression in OSCC patients and assessed the certainty of the evidence generated. In the present study, the following outcomes were investigated: overall survival (OS), disease-specific survival (DSS) and disease-free survival (DFS). For this purpose, hazard ratio (HR) used as a measure of effect and GRADE was used to assess the certainty of the evidence. As results, seven cohort studies were included in this review, 900 cases of OSCC were analyzed, whose mean age of patients was 54.63 years, predominantly male (66.33%), the site of greatest involvement being the tongue (72.7%), mean follow-up time of 60.94 months and history of smoking in 55.22% of cases. Regarding SOX2 expression, most cases classified as having increased expression (56.01%). No statistically significant association was observed between SOX2 expression and OS (p=0.53 and 0.44), DSS (p=0.74) and DFS (p=0.42). The understanding of the mechanisms by which abnormal SOX2 expression interferes with survival yet not well elucidated, and more studies with a prospective, standardized design and combined analyses needed to understand the role of this pathway in order to develop more effective therapeutic strategies.